2011
DOI: 10.1002/pd.2794
|View full text |Cite
|
Sign up to set email alerts
|

The role of three‐dimensional imaging reconstruction to measure the corpus callosum: comparison with direct mid‐sagittal views

Abstract: Reconstructed mid-sagittal views obtained by 3D multiplanar manipulations or by VCI-C are valid approaches for measuring CC length. In these views the CC should be measured as the region underneath the comma-shaped echogenic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In a recent study, Lerman‐Sagie et al 3 showed that a thick corpus callosum was always associated with other central nervous system deformities or was part of neuromagnetic syndromes among 9 cases that they evaluated. Recently, Miguelote et al 10 compared two different 3D sonographic techniques (multiplanar imaging and volume contrast imaging) to evaluate 118 measurements of a longer corpus callosum in 46 fetuses between 23 and 32 weeks' gestation, with a success rate of 91%. Their results were very similar to ours (92.7%) using the transfrontal view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Lerman‐Sagie et al 3 showed that a thick corpus callosum was always associated with other central nervous system deformities or was part of neuromagnetic syndromes among 9 cases that they evaluated. Recently, Miguelote et al 10 compared two different 3D sonographic techniques (multiplanar imaging and volume contrast imaging) to evaluate 118 measurements of a longer corpus callosum in 46 fetuses between 23 and 32 weeks' gestation, with a success rate of 91%. Their results were very similar to ours (92.7%) using the transfrontal view.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Viñals et al 9 used the trans‐frontal view with 3D sonography and reported advantages over axial acquisitions, including clear discernment between the corpus callosum and cavum septi pellucidi and better image quality due to its nature as a direct‐view plane as opposed to axial acquisitions, which are reconstructed. This fact was recently highlighted by Miguelote et al, 10 who evaluated the corpus callosum length by different 3D sonographic techniques such as multiplanar imaging and volume contrast imaging in a midsagittal view.…”
mentioning
confidence: 94%
“…On the other hand, the offline multiplanar navigation of 3D volumes can provide better visualization and recognition of normal fetal anatomy and more accurate definition of fetal abnormalities compared to 2D US (1)(2)(3)(4)(5)(6). For these reasons, this technology has been shown to be helpful for the evaluation of the fetal central nervous system (CNS) (7)(8)(9) and particularly of the posterior fossa (10)(11)(12)(13), the cortical layer (14)(15)(16)(17), midline structures (18)(19)(20) and the optic chiasm (21,22). Additionally, 3D US may provide advantages for the assessment of the face (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In malformed fetuses, a precise diagnosis was achieved with both techniques, although images obtained with VCI-A were found to be of su-displayed with variable rendering methods to better demonstrate the different anatomic structures contained within. Thus far, it has been mostly utilized to decrease artefacts and increase contrast resolution [6][7][8][9]. VCI can also be used in real-time scanning [10,11], but the mechanical four-dimensional (4D) probes thus far available have a limited image rate, causing a delay between acquisition and visualization that hampers the examinations of moving limbs.…”
Section: Introductionmentioning
confidence: 99%